Fungal Species of Botryosphaeriaceae Associated With Avocado Dieback in Southern Spain - Crespo, María; Guirado-Manzano, Lucía; Sarmiento, David; Guirado, Emilio; De-Vicente-Moreno, Antonio; Fernández-Ortuño, Dolores; Cazorla-López, Francisco Manuel; Arrebola-Díez, Eva María (Wiley, 2025)
Avocado (Persea americana) has become one of the most important subtropical crops in southern Spain. In recent years, thescarcity of irrigation water has made this crop susceptible to opportunistic diseases. This sensitivity has been associated witha series of symptoms characterised by the death of branches, mummification of fruits, cankers and reddening of the vascularbundles. To identify the aetiology of the disease, surveys have been carried out on avocado farms in the most affected areas, in-cluding Málaga and Granada (southern Spain). The surveys were conducted from 2019 to 2022. A total of 252 fungal isolates wererecovered from trees with symptoms of dieback disease. Of these isolates, 172 were initially identified by sequencing the rDNAinternal transcribed spacer (ITS) region to identify potential pathogens compatible with the symptoms. Based on the numberof isolates, the most prevalent were Neofusicoccum spp. (110 isolates) and Lasiodiplodia sp. (15 isolates), although some isolatesof Diaporthe sp. (four isolates) and Colletotrichum sp. (eight isolates) were also identified. Pathogenicity experiments in plants,branches and fruits confirmed these fungi as possible causal agents as they reproduced the symptoms found in diseased avocadocrops. The frequency of isolates associated with dieback symptoms, along with greater severity in the reproduced symptoms,shows Botryosphaeriaceae species as the main cause of dieback in avocado in southern Spain. The main objective of the presentstudy is to elucidate the aetiology of the disease to establish the infection time and thereby lay the groundwork for designingcontrol studies.
Keywords: Hongos fitopatógenos; Aguacates; Micología; Plantas -- Protección; aetiology; cankers; Lasiodiplodia sp.; Neofusicoccum spp.; pathogenicity; Persea americana